And now for something completely different. (Economist, 2018)
The article explores the popularity of Python, a computing language developed by Dutch computer scientist Guido van Rossum. According to a survey, Python is popular among professional developers and among ordinary people. The programming language is recognized for bringing coding to a new audience. The advantages and disadvantages of using Python are stated.